Ketika Gaya dan Kesadaran Menjadi Arah Baru Pilihan Konsumen - Wibowo, Erwin Sya’ban Ardi; Chua, Agus Sandro; Saputra, Christian; Jackson, Jackson; Arifin, Felix Gerrard; Lim, Stephen (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the influence of fashion consciousness on the intention to purchase secondhand shopping, with ecological consciousness functioning as a mediating variable. The increasing prominence of secondhand shopping consumption is widely associated with the notion of sustainable living, yet there remains growing concern regarding how this trend may disrupt the development and competitiveness of local fashion brands. Therefore, this study aims to explain the extent to which fashion awareness and ecological considerations shape purchasing decisions among Gen-Z consumers in Indonesia. A quantitative descriptive research method with a cross-sectional design was applied, involving 340 respondents collected through an online questionnaire. Data were processed using Structural Equation Modeling with the Partial Least Squares approach. The results demonstrate that fashion consciousness has a strong and significant influence on ecological consciousness and interest in secondhand shopping. Furthermore, ecological consciousness significantly strengthens secondhand purchase intention and mediates the relationship between fashion consciousness and sustainable shopping behavior. These findings indicate that environmental responsibility plays an essential role in transforming style-driven motivations into responsible consumption choices. The study contributes to the growing body of knowledge on sustainable consumer behavior while offering practical implications for industry stakeholders and local fashion brands to design strategies centered on sustainability, consumer education, and value-driven marketing that can enhance consumer engagement and strengthen the creative economic ecosystem.